2021
DOI: 10.1002/hpja.458
|View full text |Cite
|
Sign up to set email alerts
|

A thematic analysis of men’s help‐seeking on an Australian health helpline

Abstract: Men's health has been a popular topic of academic exploration for the majority of the past 20 years. 1 Overall, men in Australia have poorer health outcomes across a variety of indicators. Both life expectancy and health-adjusted life expectancy (HALE) are lower in Australian men than women, although the gap in HALE has decreased in recent years. Conversely, men engage with primary health services less frequently. [2][3][4] While there is some evidence that the gendered gap in help-seeking reduces when account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
4
0
1
Order By: Relevance
“…Although patients presenting with mental health symptoms have reported delaying care due to pandemic restrictions, they also have a high degree of willingness to resolve these delays through telehealth services. 35 Similar to previous studies in which men found mental health-related technologies acceptable, 14 telehealth may have partially alleviated male barriers to healthcare usage for men with anxiety symptoms in this sample. The higher likelihood of telehealth utilization among men with anxiety compared to depression has been previously observed in other populations and may be due to the passivity and low self-esteem that characterize depression.…”
Section: Strengths Limitations and Future Researchsupporting
confidence: 81%
See 1 more Smart Citation
“…Although patients presenting with mental health symptoms have reported delaying care due to pandemic restrictions, they also have a high degree of willingness to resolve these delays through telehealth services. 35 Similar to previous studies in which men found mental health-related technologies acceptable, 14 telehealth may have partially alleviated male barriers to healthcare usage for men with anxiety symptoms in this sample. The higher likelihood of telehealth utilization among men with anxiety compared to depression has been previously observed in other populations and may be due to the passivity and low self-esteem that characterize depression.…”
Section: Strengths Limitations and Future Researchsupporting
confidence: 81%
“…Telehealth services can often be discreetly accessed from any location without the need for travel, wait times, or interaction with clinic environments. While men have already reported finding other health-related technologies including health helplines and internet health information to be accessible and acceptable, 14 little is known about their use and opinions of telehealth. Given increased demand for telehealth services due to COVID 15 and its potential for reducing barriers to male healthcare access, it is important to understand men's interactions with telehealth.…”
Section: Introductionmentioning
confidence: 99%
“…Nessa perspectiva, deve-se considerar a heterogeneidade social das possibilidades de ser homem, contexto em que as masculinidades são construídas historicamente, como processo em constante transformação. Esse aspecto é fundamental para promover a equidade na atenção à saúde dos homens, o qual deve ser considerado e valorizado segundo as diferenças por idade, condição socioeconômica e étnico-racial, local de moradia urbana ou rural, situação carcerária, deficiência física e/ou intelectual, orientações sexuais e identidades de gênero não hegemônicas (4)(5)(6) .…”
Section: Introductionunclassified
“…From this perspective, the social heterogeneity of the possibilities of being a man must be considered, a context in which masculinities are historically constructed, as a process in constant transformation. This aspect is fundamental to promoting equity in men's health care, which must be considered and valued according to differences in age, socioeconomic and ethnic-racial condition, urban or rural place of residence, prison situation, physical and/or intellectual disability, sexual orientations and non-hegemonic gender identities (4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%